Group of teenage girls posing on playground equipment. - Unknown:::Creator::::::::::::
Negative shows a group of teenage girls posing on playground equipment which may be at Alum Rock Park in San Jose, California. This is possibly a picture of members of the YWCA's Contenta Hora group. Contenta Hora was a YWCA club for Latinas.